Pelatihan Pembuatan Tepung Pisang di Desa Bongo III, Kecamatan Wonosari, Kabupaten Boalemo - Alkatiri, Ramlah; Mokodompit, Nur Eng; Paramata, Sri Hantuti (Jurnal Pemberdayaan Ekonomi, 2025)
Purpose: This community engagement activity aimed to improve the knowledge and technical skills of rural communities in Desa Bongo III, Kecamatan Wonosari, Kabupaten Boalemo, in processing local agricultural produce—specifically bananas—into value-added products such as banana flour. The goal is to enhance food processing capacity while promoting local entrepreneurship. Methodology/approach: The program employed a participatory approach involving 25 community members, including housewives, village youth, and microentrepreneurs. The training introduced step-by-step banana flour production techniques: selecting ripe bananas, peeling, soaking, sun-drying bananas, and grinding them into flour using using locally available tools such as household ovens and Blender. Data were collected through participatory observation, informal interviews, and documentation and were then analyzed qualitatively. Results/findings: The training received enthusiastic responses from the participants, who quickly adapted to the processing methods. Many participants gained new insights into the economic potential of banana-based products, with several expressing interest in developing value-added derivatives, such as cookies, baby food, and cakes. The training also encouraged collaboration, increased motivation to start small businesses, and aligned with community-based development practices in the area. Conclusion: The activity effectively enhanced technical skills and opened up opportunities for economic empowerment. With sustained support, it holds promise as a model of rural microenterprise development. Limitations: Key challenges included limited access to drying and grinding equipment, dependence on weather for sun-drying, and minimal knowledge of product packaging and marketing. Contribution: The program contributes to rural development by linking local resources with practical skills, promoting entrepreneurship, and offering a replicable model for other regions aiming to empower communities through local agro-product innovation.